P59 Continuous positive airway pressure therapy in patient with excessive dynamic airway collapse: A single centre experience. (11th November 2022) - Hassan, MZ; Khurana, S; Fowler, S; Bokhari, S; Bikov, A
Abstract : Background: Excessive dynamic airway collapse (EDAC) is a potential cause for unexplained cough, breathlessness, inability to expectorate and frequent infections. Continuous positive airway pressure (CPAP) therapy is a potential treatment in EDAC; however, the evidence for long-term CPAP in adults with EDAC is weak. The aim of this service evaluation project was to assess clinical impact, tolerability, and adherence to CPAP in people with bronchoscopically confirmed (EDAC). Methods: We reviewed the clinical data of 62 patients with EDAC who were set-up on CPAP. Adherence to CPAP was compared to patient demographics and clinical characteristics. Results: Fifty patients (80%) reported improvement in their sleep, 23 patients (29%) reported improvement in their respiratory symptoms following initiation of CPAP. Thirty-eight patients (61%) were fully adherent (at least 4 hours usage on at least 70% of the days) to CPAP. The most common reasons for non-adherence included mask discomfort, nasal blockage and lack of symptoms improvement. Adherence to CPAP did not relate to demographics, the mode (auto-set or fixed) or the intensity (pressure) of CPAP, the type of interface, humidification, blood or lung function test results. Pre-CPAP sleep studies were available in 30 patients which showed high prevalence of obstructive sleep apnoea (OSA, 80%) in this population. Discussion: CPAP is usually well-tolerated and often beneficial in this group of patients and the adherence to CPAP in similar or even better than of patients with OSA. OSA may be more common in EDAC and should be regularly screened in order to have a better therapeutic response.